Application of MCDM Method in Selecting Renewable Energy - Xiang Yu, Zheng; Ho Chen, Lee; Pina, Bing; Zhang Ti, Lixiua (International journal of industrial engineering and operational research, 2023)
This paper aims to explore the application of the Multiple Criteria Decision Making (MCDM) method in the selection of renewable energy sources. The growing concern for environmental sustainability and the need to shift towards renewable energy have led to an increased interest in finding the most suitable renewable energy option. The MCDM method provides a systematic approach for evaluating and comparing various criteria related to renewable energy sources. Through a comprehensive literature review and numerical analysis, this paper examines the effectiveness of the MCDM method in supporting decision-making processes in renewable energy selection. The findings highlight the advantages, limitations, and potential areas of improvement for using MCDM techniques in the selection of renewable energy sources for different contexts.